Factors Influencing the Intention to Purchase for Eco-labeled Seafood Products in Bangkok: ปัจจัยที่มีอิทธิพลต่อความตั้งใจซื้อผลิตภัณฑ์อาหารทะเลที่ติดฉลากสิ่งแวดล้อมในกรุงเทพมหานคร - Suyanan, Warangkana; Kuldilok, Kulapa; Limsombunchai, Visit (Journal of Applied Economics and Management Strategy, 2021)
บทคัดย่อ ความต้องการในการบริโภคเพิ่มสูงขึ้นและมีความใส่ใจถึงที่มาของอาหารทะเลที่มาจากการทำประมงและการเพาะเลี้ยงจากความยั่งยืนและถูกกฎหมาย อย่างไรก็ตามการทำประมงและการเพาะเลี้ยงแบบไม่ยั่งยืนและไม่ถูกกฎหมายยังคงมีอยู่ ดังนั้นมาตรฐานจึงมีความสำคัญต่อการปรับปรุงการทำประมงรวมทั้งการจัดการ การเพาะเลี้ยงสัตว์น้ำที่ยั่งยืน ฉลากสิ่งแวดล้อมสำหรับอาหารทะเล (มาตรฐาน Marine Stewardship Council; MSC และมาตรฐาน Aquaculture Stewardship Council; ASC) เป็นมาตรฐานที่แสดงถึงการนำทรัพยากรสัตว์น้ำมาใช้อย่างยั่งยืนและเพิ่มความตระหนักของการบริโภคสัตว์น้ำ ซึ่งในประเทศไทยผู้บริโภคจำนวนน้อยที่ตระหนักถึงปัญหานี้ วัตถุประสงค์ของการศึกษาคือ ศึกษาปัจจัยที่มีอิทธิพลต่อความตั้งใจซื้อผลิตภัณฑ์อาหารทะเลที่ติดฉลากสิ่งแวดล้อมในเขตกรุงเทพมหานคร เก็บข้อมูลจากแบบสอบถามจำนวน 400 ชุด นำมาวิเคราะห์ด้วยแบบจำลองโลจิต (Logit Model) พบว่า ปัจจัยที่มีผลต่อความตั้งใจซื้อ ได้แก่ อายุ รายได้เฉลี่ยต่อบุคคลการรู้จักฉลาก MSC และฉลาก ASC พฤติกรรมเป็นมิตรต่อสิ่งแวดล้อม และทัศนคติต่ออาหารทะเลที่ติดฉลากสิ่งแวดล้อม การโฆษณาประชาสัมพันธ์สินค้าเน้นการติดฉลากโดยเฉพาะ จึงควรโฆษณาประชาสัมพันธ์ให้ข้อมูลข่าวสารเกี่ยวกับอาหารทะเลที่ติดฉลากสิ่งแวดล้อม โดยใช้สื่อโทรทัศน์ และออนไลน์ กับผู้บริโภคมากขึ้น ABSTRACT Demand for consumption has been increasing and consumers are concerned more about sustainable fishery and legal farming while fish production has faced unsustainable and illegal rules. Therefore, standards are essential in order to improve the management of fishery and aquaculture sustainability. Eco-labeled seafoods (Marine Stewardship Council; MSC and Aquaculture Stewardship Council; ASC standards) are an indicator of the sustainable use of animal resources and the increasing awareness of seafood consumption. In Thailand, consumers are still less aware of the sustainability of fish consumption. This research aims to study the factors influencing the intention to purchase eco-labeled seafood products in Bangkok. Collect data from 400 questionnaires were analyzed using the logit model. The results revealed that the factors influencing the intention to purchase were age, personal income, knowing about MSC and ASC labels, environmentally friendly behaviors, attitudes toward eco-labeled seafood, and advertisement focusing on labeling in particular. Therefore, advertising and publicizing news about eco-labeled seafood products should be applied to various media such as television and online media in order to inform consumers.